Study of Reaction Kinetics of Magnesium Sulfate Formation from Bittern and Sulfate Acid (Nusantara Science and Technology Proceedings)
Bittern is a concentrated liquid obtained from the salt plant waste, and the amount is abundant. Bittern contains various minerals; this mineral occurs because it does not crystallize during the manufacture of salt. The minerals have high concentrations, among others: Magnesium (Mg), Sodium (Na), and Calcium (Ca). In general (28.5 – 30 oBe) is still contained Magnesium about 4-5% w/v. Considered the high content of Mg on Bittern is worth as the raw material for the manufacture of MgSO4. In this study, Mg(OH)2 was obtained by reacting Bittern with NaOH to obtain Mg(OH)2 deposits. The study aims to determine the reaction rate constant and activation energy of the formation of Magnesium Sulfate. The prescribed variable is Mg(OH)2 46.6 gr; NaOH 4N 3 liters; H2SO4 1N 500 ml; Drying temperature 100oC; Stirring speed of 110 rpm. As for the modified variable, temperature: 40, 45, 50, 55, 60oC and stirring time: 20, 30, 40, 50, 60 minutes. The best result for forming magnesium sulfate is at temperature 60oC and 60 minutes with reaction conversion (xA) 26.9%. The formation of magnesium sulfate followed the second-order reaction and the equation of the rate constant k = 0.00512 min-1 and the activation energy of 131.394 kJ/mol.K.